Transparent material and preparation method and application thereof

By using polyimide materials and performing acid anhydride capping and hydroxyl or epoxy-reactive esterification, the existing adhesives/coats have been solved inadequate heat resistance and aging resistance at high temperatures, and a transparent material with high Tg point and aging resistance characteristics is achieved, ensuring stability and reliability in high temperature environments.

CN119775555APending Publication Date: 2025-04-08BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411066720.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing adhesives/coatings have poor heat resistance and aging resistance under high temperature environments, which are prone to softening at high temperatures and lead to a decrease in adhesion and cohesion, which leads to separation or cracking.

Method used

Polyimide is used as the main structure and esterification by acid anhydride endoprotection and hydroxyl or epoxy reaction to prepare a transparent material with high Tg point and aging resistance.

Benefits of technology

It improves the stability of the material in high-temperature environment, avoids the problem of decreasing adhesion and cohesion, and ensures the reliability and durability of the material under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a transparent material and a preparation method and application thereof.The transparent material takes polyimide as a main body structure, the two ends of the molecular weight of the polyimide are terminated through acid anhydride, then the polyimide reacts with hydroxyl for esterification or reacts with epoxy for ring opening, and the transparent material has the advantages of being resistant to aging and high in Tg point and can be applied to special high-temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optical materials, and in particular to a transparent material and a preparation method and application thereof. Background Art

[0002] Adhesives / coatings on the market are mainly used for display touch screens, LED packaging, camera lens fixation, or other parts that require fast curing. The main components of adhesives / coatings are structurally divided into: acrylates, polyurethanes, silicones, rubbers and epoxy resins; the main formula composition is: main resin + active diluent + initiator + and / or catalyst + other additives. Most adhesives / coatings are cured by one or a combination of thermal curing, UV curing, and moisture curing.

[0003] The above products have the following major disadvantages: acrylates, polyurethanes, rubbers and epoxy resins have poor heat resistance, aging resistance and UV aging resistance; while silicones generally have low adhesion and cannot be used in many scenarios.

[0004] Therefore, in order to overcome the above shortcomings, some improved products have appeared on the market. However, most of the existing improved products have a low Tg temperature, usually <100°C, which quickly softens in a high temperature environment, causing the adhesive force and cohesive force to decrease, resulting in separation or cracking. Summary of the invention

[0005] The embodiments of the present application provide a transparent material and a preparation method and application thereof, which improve the Tg temperature to solve the technical problem of rapid softening of the adhesive force and decreased cohesive force in a high temperature environment, leading to separation or cracking.

[0006] In order to achieve the above-mentioned object, in a first aspect, an embodiment of the present application provides a transparent material, comprising a polymer as shown in formula (1-1): Formula (1-1); In formula (1-1), R is independently selected from reactive groups containing hydroxyl or epoxy functional groups; A is independently selected from dibasic acid anhydrides; M is independently selected from diamines; The value range of n is 1 to 20000.

[0007] Some embodiments of the present application provide a transparent polyimide material, which uses polyimide as the main structure, uses anhydride to end-cap the two ends of the polyimide molecular weight, and then reacts with hydroxyl groups for esterification or with epoxy for ring opening. The material has the characteristics of aging resistance and high Tg point, and can be used in special high-temperature environments.

[0008] Optionally, in some embodiments of the present application, the reactive group includes one or more functional groups selected from the group consisting of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane.

[0009] Optionally, in some embodiments of the present application, the dibasic acid anhydride includes one or more of a dibasic acid anhydride containing an aliphatic ring, a fluorine-containing dibasic acid anhydride or an aromatic dibasic acid anhydride.

[0010] Optionally, in some embodiments of the present application, the dibasic acid anhydride includes one or more of cyclobutanetetracarboxylic dianhydride, bicyclo[2.2.1]-heptane-2-methylcarboxylic acid-3,5,6-tricarboxy-2,3,5,6-dianhydride, difluorophthalic anhydride, hexafluorodianhydride, and pyromellitic dianhydride.

[0011] Optionally, in some embodiments of the present application, the diamine includes one or more of a diamine containing an aliphatic ring, a fluorine-containing diamine, an aliphatic diamine or an aromatic diamine.

[0012] Optionally, in some embodiments of the present application, the diamine includes one or more of 1,2-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, hexamethylenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.

[0013] Optionally, in some embodiments of the present application, the value range of n is 100 to 5000.

[0014] Optionally, in some embodiments of the present application, the value range of n is 100 to 3000.

[0015] In a second aspect, an embodiment of the present application provides a method for preparing a transparent material, comprising the following steps: Providing anhydride terminated polyimide materials; The anhydride-terminated polyimide material is re-terminated by R to obtain a transparent material; Wherein, R is independently selected from one or more functional groups of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane containing hydroxyl or epoxy functional groups.

[0016] Optionally, in some embodiments of the present application, the raw material of R includes one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, glycidyl methacrylate, and cyclohexane-1,2-dicarboxylic acid diglycidyl ester.

[0017] Optionally, in some embodiments of the present application, the anhydride terminated polyimide material is prepared by the following method: The diamine is reacted with the dibasic acid anhydride to prepare a transparent polyamic acid solution; A dehydrating agent and a catalyst are added to a transparent polyamic acid solution to react, and the mixture after the reaction is poured into a precipitant and filtered to obtain an anhydride-terminated polyimide material.

[0018] Optionally, in some embodiments of the present application, the molar ratio of the dibasic acid anhydride to the diamine is in the range of 1.0003-1.03.

[0019] Specifically, the molar ratio of the dibasic acid anhydride to the diamine is in the range of any one of 1.0003, 1.0005, 1.008, 1.001, 1.003, 1.005, 1.008, 1.01, 1.012, 1.015, 1.017, 1.02, 1.025, 1.03 or in the range between any two of them.

[0020] In a third aspect, an embodiment of the present application provides a composition, comprising the following components in parts by weight: Such as the aforementioned transparent material 10-90 parts, initiator 0-5 parts, active diluent 5-70 parts, catalyst 0-5 parts and auxiliary agent 0-10 parts.

[0021] In a fourth aspect, embodiments of the present application provide a use of the aforementioned transparent material or the aforementioned composition in an adhesive or a coating.

[0022] In the transparent material of the embodiment of the present application, polyimide is used as the main structure, and acid anhydride is used to end-cap the two ends of the polyimide molecular weight, and then reacts with hydroxyl groups for esterification or reacts with epoxy for ring opening. It has the characteristics of aging resistance and high Tg point, and can be used in special high-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0023] Figure 1 is a chemical reaction schematic diagram of S100 in some embodiments of the present application; Figure 2 is a chemical reaction schematic diagram of S200 in some embodiments of the present application; Figure 3 is a chemical reaction schematic diagram of S300 in some embodiments of the present application; Figure 4 It is a picture of the samples of Examples 1-3 before the shear strength test. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0025] Most adhesives / coatings on the market are acrylates, polyurethanes, rubbers, epoxies and silicones. Among them, acrylates, polyurethanes, rubbers and epoxies have poor heat resistance, aging resistance and UV resistance; while silicones generally have low adhesion and cannot be used in many scenarios.

[0026] Transparent polyimide is widely used in the field of optical films. Its molecular structure has high Tg and aging resistance compared to other components, and has natural advantages in certain high-temperature environments, but it is rarely used in the adhesive / coating field on the market. This application uses transparent polyimide as the main structure, so that it can be used to prepare adhesives / coatings suitable for high-temperature and aging-resistant environments.

[0027] In a first aspect, the present application provides a transparent material, comprising a polymer as shown in formula (1-1): Formula (1-1).

[0028] In some embodiments of the present application, in the above technical solution, the structure shown in formula (1-1) can be used as a structural unit from left to right, or from right to left.

[0029] In some embodiments of the present application, R is independently selected from reactive groups containing hydroxyl groups or epoxy functional groups.

[0030] In some embodiments of the present application, the reactive group includes one or more functional groups selected from the group consisting of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane.

[0031] In some embodiments of the present application, A is independently selected from dibasic acid anhydrides.

[0032] In some embodiments of the present application, the dibasic acid anhydride includes one or more of a dibasic acid anhydride containing an aliphatic ring, a fluorine-containing dibasic acid anhydride or an aromatic dibasic acid anhydride.

[0033] Specifically, A is independently selected from one or more of cyclobutanetetracarboxylic dianhydride, bicyclo[2.2.1]-heptane-2-methylcarboxylic acid-3,5,6-tricarboxy-2,3,5,6-dianhydride, difluorophthalic anhydride, hexafluorodianhydride, and pyromellitic dianhydride.

[0034] In some embodiments of the present application, M is independently selected from diamines.

[0035] In some embodiments of the present application, the diamine includes one or more of a diamine containing an aliphatic ring, a fluorine-containing diamine, an aliphatic diamine or an aromatic diamine.

[0036] Specifically, the diamine includes one or more of 1,2-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, hexamethylenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.

[0037] In some embodiments of the present application, the value of n ranges from 100 to 5000.

[0038] In some embodiments of the present application, the value of n ranges from 100 to 3000.

[0039] When the value of n is within the above preferred range, the molecular chain length is moderate, the resin has better flexibility, and the material viscosity is highly applicable, and no more diluent is required for dilution, thereby maintaining better performance.

[0040] It should be noted that suitable A and M can be selected according to different applications and required compositions to ensure that the product is colorless and transparent.

[0041] In a second aspect, the present application also provides a method for preparing a transparent material, comprising the following steps: Providing anhydride terminated polyimide materials; The anhydride-terminated polyimide material is re-terminated by R to obtain a transparent material; Wherein, R is independently selected from one or more functional groups of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane containing hydroxyl or epoxy functional groups.

[0042] In some embodiments of the present application, the raw material of R includes one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, glycidyl methacrylate, and cyclohexane-1,2-dicarboxylic acid diglycidyl ester.

[0043] In some embodiments of the present application, the method for preparing the transparent material comprises the following steps: S100, reacting diamine with dibasic acid anhydride to obtain a transparent polyamic acid solution, see Figure 1 ; S200, adding a dehydrating agent and a catalyst to a transparent polyamic acid solution to react, pouring the reaction mixture into a precipitant, filtering, and obtaining an anhydride-terminated polyimide material, see Figure 2 ; S300, taking a certain amount of anhydride-terminated transparent polyimide material, adding a solvent, a catalyst and R2 with an active functional group to react; Figure 3 ; S400, vacuuming to remove the solvent to obtain a transparent material.

[0044] In some embodiments of the present application, the transparent material is a colorless transparent material.

[0045] In step S100, the diamine is dissolved in the solvent by adding the diamine and the solvent into a beaker respectively, and stirring at -10-10°C for 20-30 minutes to fully dissolve the diamine. Specifically, the dissolving temperature is preferably 0°C.

[0046] In step S100, the molar ratio of the dibasic acid anhydride to the diamine is in the range of 1.0003-1.03, so as to achieve anhydride end-capping of the colorless and transparent polyimide.

[0047] In step S100, the reaction is carried out under vacuum conditions, first evacuating the air and then introducing argon gas to remove oxygen in the reaction device.

[0048] In step S100, the reaction is carried out at -10-10°C for 1-5 hours, and then at room temperature for 12-36 hours. Specifically, the reaction is carried out at 0°C for 2 hours, and then at room temperature for 24 hours.

[0049] In step S200, the reaction is vacuumed multiple times before the reaction, and argon gas is introduced to remove oxygen in the reaction device.

[0050] In step S200, the reaction time is 12 hours.

[0051] In step S200, the dehydrating agent may be acetic anhydride.

[0052] In step S200, the catalyst may be triethylamine.

[0053] In step S200, the precipitant may be one of ethanol, ethylene glycol, and glycerol.

[0054] In step S300, R2 is independently selected from one or more functional groups of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane containing hydroxyl or epoxy functional groups. The raw material of R2 can be a single monomer or a mixture of multiple monomers, including but not limited to the following common substances: hydroxyethyl acrylate, hydroxyethyl methacrylate, glycidyl methacrylate, pure water, etc.

[0055] In step S300, the reaction temperature is 100-150°C, and the reaction time is 0.5-24h.

[0056] In step S300 , if the acid value of the transparent polyimide resin is m, 0<molar amount (R2+R3)<5m is satisfied.

[0057] In step S400, the solvent is removed under vacuum at 60-120°C.

[0058] In a third aspect, the present application further provides a composition, comprising the following components in parts by weight: 10-90 parts of the aforementioned transparent material, 0-5 parts of initiator, 5-70 parts of active diluent, 0-5 parts of catalyst and 0-10 parts of auxiliary agent.

[0059] In some specific embodiments, the composition includes the following components in percentage by weight: The aforementioned transparent material 10-90%, initiator 0.5-5%, diluent 5-70%, catalyst 0.5-5% and silane coupling agent 0.5-1%.

[0060] In some specific embodiments, the composition includes the following components in percentage by weight: The aforementioned transparent material 10-90%, initiator 0.5-5%, diluent 5-70%, catalyst 0.5-5% and antioxidant 0.5-1%.

[0061] In some specific embodiments, the composition includes the following components in percentage by weight: The aforementioned transparent material 10-90%, initiator 0.5-5%, diluent 5-70%, catalyst 0.5-5% and antioxidant 0.5-1%.

[0062] In some specific embodiments, the composition includes the following components in percentage by weight: The aforementioned transparent material 10-90%, initiator 0.5-5%, diluent 5-70%, cross-linking agent 1-10%, catalyst 0.5-5% and antioxidant 0.5-1%.

[0063] In some embodiments of the present application, the initiator may include one of a photoinitiator and a thermal initiator.

[0064] In some embodiments of the present application, the photoinitiator includes but is not limited to 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and one or more mixtures thereof.

[0065] In some embodiments of the present application, the thermal initiator includes but is not limited to a mixture of one or more of benzoyl peroxide, cumene hydroperoxide, di-tert-butyl peroxide, tert-butyl perbenzoate, methyl ethyl ketone peroxide, diisopropyl peroxydicarbonate, etc.

[0066] In some embodiments of the present application, the diluent includes but is not limited to a mixture of one or more of acrylates, methacrylates, vinyl ethers, alkoxy epoxy monomers, aromatic epoxy monomers, and the like.

[0067] In some embodiments of the present application, the catalyst includes but is not limited to tertiary amine catalysts, transition metal organic compounds: iron acetylacetonate, triphenyl bismuth, and the like.

[0068] In some embodiments of the present application, the other auxiliary agents include but are not limited to a mixture of one or more of silane coupling agents, leveling agents, defoaming agents, antioxidants, etc.

[0069] In a fourth aspect, embodiments of the present application provide a use of the aforementioned transparent material or the aforementioned composition in an adhesive or a coating.

[0070] In some embodiments of the present application, the adhesive may be a colorless transparent polyimide adhesive cured by ultraviolet light, a colorless transparent polyimide adhesive cured by ultraviolet light and heat, or a colorless transparent polyimide adhesive cured by ultraviolet light and moisture.

[0071] In some embodiments of the present application, the coating may be a colorless transparent polyimide coating cured by ultraviolet light, a colorless transparent polyimide coating cured by ultraviolet light and heat, or a colorless transparent polyimide coating cured by ultraviolet light and moisture.

[0072] In some embodiments of the present application, the present application provides a UV-curable adhesive, comprising 10-90% of the aforementioned transparent material, 0.5-5% of a photoinitiator, 5-70% of an active diluent, and 0.5-10% of other additives.

[0073] In some embodiments of the present application, the raw material of R in the transparent material is selected from acrylate containing hydroxyl / epoxy functional groups or epoxy resin containing hydroxyl / epoxy functional groups.

[0074] In some embodiments of the present application, the present application provides a thermosetting adhesive, comprising the aforementioned transparent material, a thermal initiator, an epoxy cross-linking agent, a reactive diluent and other additives; wherein the raw material of R in the transparent material is selected from an acrylate containing a hydroxyl / epoxy functional group or an epoxy resin containing a hydroxyl / epoxy functional group.

[0075] In some embodiments of the present application, the present application provides a moisture-curing adhesive, including the aforementioned transparent material, a cross-linking agent, a catalyst, an active diluent and other additives; wherein the raw material of R in the transparent material is selected from a silane coupling agent containing a hydroxyl / epoxy functional group.

[0076] In some embodiments of the present application, the present application provides a multi-curing adhesive, including the aforementioned transparent material, a multi-functional initiator, an active diluent and other additives; wherein the transparent material includes an acrylate / epoxy resin containing a hydroxyl / epoxy functional group, a silane coupling agent containing a hydroxyl / epoxy functional group, a cyanoacrylate containing a hydroxyl / epoxy functional group, and a modified material with multiple active groups obtained by capping a colorless and transparent polyimide with cyclopentadiene.

[0077] In addition, the present application may also provide an injection moldable optical product, including an optical lens made of the above transparent polyimide material. Specifically, it may be an optical lens.

[0078] The present application is described in detail below by means of specific examples, which are only partial examples of the present application and are not intended to limit the present application. The raw materials used in the following examples are all commercially available products unless otherwise specified.

[0079] Example 1 A colorless and transparent ultraviolet curing polyimide adhesive is prepared by the following method: S100, 2,2-bis(trifluoromethyl)diaminobiphenyl (28.820 g, 0.09 mol), hexamethylenediamine (1.16 g, 0.01 mol) and solvent dimethylacetamide (358 g) were added to a flask respectively, and stirred at 0 °C for 20-30 min to fully dissolve; then hexafluorodianhydride (45.312 g, 0.102 mol) was added, and after multiple vacuum treatments, the vacuum condition was to pass argon gas to remove oxygen in the reaction device, react at 0 °C for 2 h, and then react at room temperature for 24 h to obtain a transparent polyamic acid (PAAs) solution; S200, add acetic anhydride (86 g) and triethylamine (32 g) to a transparent polyamic acid (PAAs) solution, vacuum for several times, pass argon to remove oxygen in the reaction device, continue the reaction for 12 h, slowly pour the reaction mixture into ethanol, precipitate a white filamentous precipitate, filter it out, and dry it to obtain an anhydride-terminated polyimide material; S300, add the anhydride-terminated polyimide material into a four-necked flask, add solvent dimethylacetamide (100 g), catalyst p-toluenesulfonic acid (0.0096 g) and hydroxyethyl acrylate (0.48 g), pass through vacuum several times, pass argon to remove oxygen in the reaction device, and reflux at 110-120°C for 4 h; S400, removing the solvent by vacuum at 60-120° C. to obtain a colorless and transparent polyimide material modified by acrylic acid; S500, take 50 g of acrylic acid-modified colorless transparent polyimide material, add 38 g of isobornyl methacrylate, 5 g of 1,3,5-triacryloylhexahydro-1,3,5-triazine, 0.5 g of photoinitiator TPO, 0.1 g of photoinitiator 811, 0.4 g of triethyl phosphite, 3 g of antioxidant 1010, and 3 g of 1,6-hexanedithiol, and mix thoroughly under argon conditions to obtain a UV-curable colorless transparent polyimide adhesive.

[0080] Example 2 A colorless and transparent polyimide adhesive with ultraviolet and heat dual curing is prepared by the following method: S100, 2,2-bis(trifluoromethyl)diaminobiphenyl (28.820 g, 0.09 mol), hexamethylenediamine (1.16 g, 0.01 mol) and solvent dimethylacetamide (358 g) were added to a flask respectively, and stirred at 0 °C for 20-30 min to fully dissolve; then hexafluorodianhydride (45.312 g, 0.102 mol) was added, and after multiple vacuum treatments, the vacuum condition was to pass argon gas to remove oxygen in the reaction device, react at 0 °C for 2 h, and then react at room temperature for 24 h to obtain a transparent polyamic acid (PAAs) solution; S200, add appropriate amount of acetic anhydride (86 g) and triethylamine (32 g) to the transparent polyamic acid (PAAs) solution, vacuum for several times, pass argon to remove oxygen in the reaction device, continue the reaction for 12 h, slowly pour the reaction mixture into ethanol, precipitate white filamentous precipitate, filter and dry to obtain anhydride-terminated polyimide material; S300, add the anhydride-terminated polyimide material into a four-necked flask, add solvent dimethylacetamide (100 g), catalyst p-toluenesulfonic acid (0.0096 g) and hydroxyethyl acrylate (0.3 g), vacuum for several times, pass argon to remove oxygen in the reaction device, and reflux at 110-120 °C for 4 h; S400, removing the solvent by vacuum at 60-120°C to obtain a colorless and transparent polyimide material modified by acrylic acid; S500, take 20 g of acrylic acid modified colorless transparent polyimide material, add bisphenol A epoxy resin (Dow DER664UE) 40 g, isobornyl methacrylate 24 g, 1,3,5-triacryloyl hexahydro-1,3,5-triazine 5 g, photoinitiator TPO 0.5 g, photoinitiator 811 0.1 g, triethyl phosphite 0.4 g, antioxidant 1010 3 g, 1,6-hexanedithiol 3 g and epoxy accelerator 4 g (American Air Chemical Ancamide K54), mix thoroughly under argon conditions, and then store at -45--15 ° C to obtain a UV-heat dual-cured colorless transparent polyimide adhesive.

[0081] Example 3 A colorless and transparent ultraviolet-moisture dual-curing polyimide adhesive is prepared by the following method: S100, 2,2-bis(trifluoromethyl)diaminobiphenyl (28.820 g, 0.09 mol), hexamethylenediamine (1.16 g, 0.01 mol) and solvent dimethylacetamide (358 g) were added to a flask respectively, and stirred at 0 °C for 20-30 min to fully dissolve; then hexafluorodianhydride (45.312 g, 0.102 mol) was added, and after multiple vacuum treatments, the vacuum condition was to pass argon gas to remove oxygen in the reaction device, react at 0 °C for 2 h, and then react at room temperature for 24 h to obtain a transparent polyamic acid (PAAs) solution; S200, add appropriate amount of acetic anhydride (86 g) and triethylamine (32 g) to the transparent polyamic acid (PAAs) solution, vacuum for several times, pass argon to remove oxygen in the reaction device, continue the reaction for 12 h, slowly pour the reaction mixture into ethanol, precipitate white filamentous precipitate, filter and dry to obtain anhydride-terminated polyimide material; S300, adding the anhydride-terminated polyimide material into a four-necked flask, adding 100 g of dimethylacetamide as solvent, 0.0096 g of p-toluenesulfonic acid as catalyst, 0.3 g of hydroxyethyl acrylate and 0.48 g of γ-glycidyloxypropyltrimethoxysilane, passing through vacuum several times, passing argon to remove oxygen in the reaction device, and refluxing at 110-120 °C for 4 h; S400, removing the solvent by vacuum at 60-120° C. to obtain a colorless and transparent polyimide material modified by acrylic acid / siloxane; S500, take 50 g of colorless transparent polyimide material modified by acrylic acid / siloxane, 37.5 g of isobornyl methacrylate, 5 g of 1,3,5-triacryloylhexahydro-1,3,5-triazine, 0.5 g of photoinitiator TPO, 0.1 g of photoinitiator 811, 0.4 g of triethyl phosphite, 3 g of antioxidant 1010, 3 g of 1,6-hexanedithiol and 0.5 g of dibutyltin dilaurate to prepare a UV-moisture dual-curing colorless transparent polyimide adhesive.

[0082] Comparative Example 1 A polyimide material, which is different from Example 1 in that the ratio of anhydride to diamine is 1:1, and the end-capping reaction and formula preparation of S300-S500 in the experiment are not performed, and the solvent dimethylformamide is simply added for dilution to finally prepare the polyimide material.

[0083] Comparative Example 2 A polyimide material, which is different from Example 2 in that the ratio of anhydride to diamine is 1:1, and the end-capping reaction and formula preparation of S300-S500 in the experiment are not performed, and the solvent dimethylformamide is simply added for dilution to finally prepare the polyimide material.

[0084] Comparative Example 3 A polyimide material, which is different from Example 3 in that the ratio of anhydride to diamine is 1:1, and the end-capping reaction and formula preparation of S300-S500 in the experiment are not performed, and the solvent dimethylformamide is simply added for dilution to finally prepare the polyimide material.

[0085] Comparative Example 4 A polyimide material is prepared in the same manner as in Comparative Example 1.

[0086] Comparative Example 5 A polyimide material is prepared in the same manner as in Comparative Example 2.

[0087] Comparative Example 6 A polyimide material is prepared in the same manner as in Comparative Example 3.

[0088] Detection methods: (1) b value test (Lab test): Tested in accordance with GB / T 3181-2008 Paint Film Color Standard; (2) Clarity test: in accordance with GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics"; (3) Tg test: in accordance with GB / T 1634-2004 "Determination of glass transition temperature of plastics"; (4) Shrinkage test: in accordance with GB / T 24148.9-2014 "Plastic unsaturated polyester (UP-R) Part 9: Determination of total volume shrinkage"; (5) Hardness test: in accordance with GB / T 2411-2008 "Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a hardness tester"; (6) Shear force test: in accordance with GB / T 7124-2008 "Determination of tensile shear strength (rigid material to rigid material)".

[0089] The test results are shown in Table 1: Table 1

[0090] Combining the test results of Example 1, Comparative Example 1 and Table 1, it can be seen that the dibasic acid anhydride in Example 1 adopts hexafluorodianhydride, which has a high fluorine content and is helpful for preparing a highly transparent polyimide material. The molar ratio of anhydride to diamine is 1.02:1, and an anhydride-terminated polyimide material is obtained; 38 g of isobornyl methacrylate and 1,3,5-triacryloylhexahydro-1,3,5-triazine are added to make it contain an unsaturated double bond, and then the corresponding photoinitiator is added to achieve ultraviolet curing, and at the same time, a high shear strength can still be maintained under the condition of @120℃ / PC+PC; while Comparative Example 1 lacks subsequent reaction, that is, lacks active groups, and therefore ultraviolet curing cannot be achieved, and the shear strength is low under the condition of @120℃ / PC+PC.

[0091] Combining the test results of Example 2, Comparative Example 2 and Table 1, it can be seen that the sample of Example 2 contains both unsaturated double bonds and epoxy functional groups, the unsaturated double bonds can be cured by ultraviolet rays, and the epoxy functional groups can be thermally cured by adding a crosslinking agent / catalyst.

[0092] Combining the test results of Example 3, Comparative Example 3 and Table 1, it can be seen that the sample of Example 3 contains both unsaturated double bonds and oxysilane bonds. The unsaturated double bonds can be cured by ultraviolet light, and the oxysilane bonds can be dealcoholized and cured in the presence of a crosslinking agent / catalyst.

[0093] Combining Examples 1-3, Comparative Examples 1-3 and the b value in Table 1, it can be seen that the colors of Examples 1-3 after adding active reactive groups are close to the original polyimide, indicating that the modification method of the present application does not affect the color of the colorless and transparent polyimide.

[0094] Figure 4This is a picture of samples during the shear strength test of Examples 1-3 of the present application. In the picture, the yellow color is the limited thickness polyimide tape, and the middle is the polyimide adhesive.

[0095] Combining the test results of Examples 1-3, Comparative Examples 1-3 and Table 1, it can be seen that the Tg of Examples 1-3 is 170-210°C, while the Tg of the samples of Comparative Examples 1-3 is 160°C-170°C, so Comparative Examples 1-3 are not completely cured at 150°C.

[0096] Comparative Examples 4 to 6 were cured at 240° C. for 30 min. Since the curing temperature was relatively high, sufficient curing could be achieved, and the Tg temperature reached above 260° C. However, since the PC substrate melted and deformed at 240° C., the shear strength could not be tested.

[0097] The transparent material, preparation method and application thereof provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technicians in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A transparent material, characterized in that: Including a polymer as shown in formula (1-1): Formula (1-1); In formula (1-1), R is independently selected from reactive groups containing hydroxyl or epoxy functional groups; A is independently selected from dibasic acid anhydrides; M is independently selected from diamines; The value range of n is 1 to 20000.

2. The transparent material according to claim 1, characterized in that The reactive groups include one or more functional groups selected from the group consisting of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane.

3. The transparent material according to claim 1, characterized in that The dibasic acid anhydride includes one or more of a dibasic acid anhydride containing an aliphatic ring, a fluorine-containing dibasic acid anhydride or an aromatic dibasic acid anhydride.

4. The transparent material according to claim 3, characterized in that The dibasic acid anhydride includes one or more of cyclobutanetetracarboxylic dianhydride, bicyclo[2.2.1]-heptane-2-methylcarboxylic acid-3,5,6-tricarboxy-2,3,5,6-dianhydride, difluorophthalic anhydride, hexafluorodianhydride, and pyromellitic dianhydride.

5. The transparent material according to claim 1, characterized in that The diamine includes one or more of a diamine containing an aliphatic ring, a fluorine-containing diamine, an aliphatic diamine or an aromatic diamine.

6. The transparent material according to claim 5, characterized in that The diamine includes one or more of 1,2-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, hexamethylenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.

7. The transparent material according to claim 1, characterized in that The value range of n is 100 to 5000.

8. The transparent material according to claim 7, characterized in that The value range of n is 100 to 3000.

9. A method for preparing a transparent material according to any one of claims 1 to 8, characterized in that: The steps include: Providing anhydride terminated polyimide materials; The anhydride-terminated polyimide material is re-terminated by R to obtain a transparent material; Wherein, R is independently selected from one or more functional groups of acryloyloxy, methacryloyloxy, epoxy, acrylonitrile, cyclopentadienyl, and siloxane containing hydroxyl or epoxy functional groups.

10. The method for preparing a transparent material according to claim 9, characterized in that: The raw material of R includes one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, glycidyl methacrylate, and cyclohexane-1,2-dicarboxylic acid diglycidyl ester.

11. The method for preparing a transparent material according to claim 9, characterized in that: The anhydride terminated polyimide material is prepared by the following method: The diamine is reacted with the dibasic acid anhydride to prepare a transparent polyamic acid solution; A dehydrating agent and a catalyst are added to a transparent polyamic acid solution to react, and the mixture after the reaction is poured into a precipitant and filtered to obtain an anhydride-terminated polyimide material.

12. The method for preparing a transparent material according to claim 11, characterized in that: The molar ratio of the dibasic acid anhydride to the diamine ranges from 1.0003 to 1.

03.

13. A composition, characterized in that The composition comprises the following components in parts by weight: 10-90 parts of the transparent material according to any one of claims 1-9, 0-5 parts of an initiator, 5-70 parts of a reactive diluent, 0-5 parts of a catalyst and 0-10 parts of an auxiliary agent.

14. Use of the transparent material according to any one of claims 1 to 8 or the composition according to claim 13 in an adhesive or a coating.